Platinum Nanoflower-Modified Electrode as a Sensitive Sensor for Simultaneous Detection of Lead and Cadmium at Trace Levels - Thi Lieu Nguyen; Van Hoang Cao; Thi Hai Yen Pham; Truong Giang Le (My University, 2019)
Platinum Nanoflower-Modified Electrode as a Sensitive Sensor for Simultaneous Detection of Lead and Cadmium at Trace Levels
Keywords: Pt Nanoflower